Efektivitas Metode Tucker Turtle Dalam Menstimulasi Kemampuan Regulasi Emosi Anak Usia 5-6 Tahun - Nur'Afiah, Az-Zahra; Mirawati, Mirawati; AM, Muh. Asriadi (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
Emotion regulation is a child's ability to recognize, understand, and express emotions adaptively. In children aged 5-6 years, the inability to manage emotions can trigger behavioral problems, adaptation difficulties, and obstacles in the learning process. The situation in the field shows that many preschool children often experience tantrums, have difficulty cooperating, or overreact when facing conflicts. This study aims to observe the effectiveness of the Tucker Turtle method in stimulating children's emotion regulation skills. The application of the Tucker Turtle method has not been widely explored as well as the use of effect size analysis to measure the practical impact of the intervention. The study used a quasi-experimental design, involving an experimental group (Tucker Turtle method intervention) and a control group (conventional method). Data collection techniques were carried out through pre-test and post-test observations, then analyzed using independent t-test and effect size test. The results showed that based on the independent t-test (p = 0.54), there was no statistically significant difference. However, the effect size of 0.924 indicated a large practical impact. The conclusion of the study confirmed that the Tucker Turtle method can be an alternative to stimulate children's ability to manage their emotions compared to conventional methods.